Anti-cancer and Anti-venom Analysis of a Gedunin - Dagar P.; Mishra A. (My University, 2025)
Background: A member of the Malvaceae family, Azadirachta indica (Neem) is well-known for its secondary metabolites, including limonoids, flavonoids, triterpenoids, and tetraterpe-noids. These compounds have been studied for decades for their bioactivities, including antihemor-rhagic and antiproteolytic, which provide information about the use of triterpenoids. Methods: Gedunin was purified by chromatography after being extracted using the Soxhlet method to ensure that it was present in the fruit of the (neem) A. indica plant. ICM Molsoft was used to test the substance for a potential inhibitory effect on the enzymes found in all species of snake venom, including 5'-nucleotidase, acetylcholinetrace, L-aao, metalloproteinase, Results: Our goal is to forecast the pharmacological characteristics of gedunin, which has demon-strated a wide range of activities as a possible antidote for treating patients with snake bites. Our research also shows gedunin has some anti-cancer action in experiments using the cell line HepG2. Conclusion: Gedunin has potential as a medication. © 2023 Bentham Science Publishers.